THE PERCEPTION OF THE VISITOR EXPERIENCE AT THE PURA PUSEH BATUAN IN GIANYAR BALI AS A TOURIST ATTRACTION - I Ketut Muliadiasa (Jurnal Ilmiah Hospitality Management, 2015)
The aim of this study was to describe the visitors experience during their visit to ‘The Pura Puseh Batuan’ as tourist destination in Gianyar, Bali regency on, and was to describe the management of ‘The Pura Puseh Batuan’ temple as one of cultural tourist attractions in Gianyar, Bali The theoretical review is perception theoretical review is based on costumer’s experience that refers to the seven of variables such as hedonism, novelty, local culture, refreshment, meaningfulness, involvement, and knowledge.This study used primer data with the survey method by interviewing the personals who manage ‘The Pura Puseh Batuan’ and by using the questioners which were obtained from the visitor through the sampling of quota were 60 respondents.  By using the class of interval technique would be obtained mean, it would show each variable level was studied and score to deviation standard.The result of this studied showed that there were two variables, Hedonism and Novelty which obtained poor score to its indicators with mean of 1.0.   The visitors did not feel getting involved in these activities, this means they did not obtain interesting experience.  The score of the variables such as local culture, refreshment, meaningfulness, and knowledge had 3.23 score in average category, for the involvement variable had good category was 3.49. The deviation standard of all variable had the score under 1 (one) which showed the data score clustered around average or mean and had a low deviation of mean.The implication of this study positively would be responded by the management of “The Pura Puseh Batuan’ to improve their tourist attraction by giving priority to the values of the temple as an entity which is sanctified by Hindus people on Bali.